ANALISIS PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MOTOR HEPY CABANG JAWA TENGAH - Murdiyanto, Agus (Jurnal Ilmiah Telaah Manajemen, 2012)
This study aims to analyze the effect of Work Motivation and Work Environment on Employee Performance. This study uses primary data by distributing questionnaires to employees Hapi Motor Branch of Central Java with respondents overall employee Motor Hapy the census. Test Result Statistics independent sample t-test showed the influence of hypothesis testing work motivation on employee performance can be summed up in partial Work Motivation significant positive effect on employee performance variables. Hypothesis testing effect on Employee Performance Work Environment concluded in partial Workplace significant positive effect on employee performance variables. Results of R Square of 0.76 this means that 76% of variation can be explained by the Employee Performance variation of the two independent variables Work Motivation and Work Environment. While the remaining 24% is explained by reasons - other causes outside the model. Keywords: Work Motivation, Work Environment and Employee Performance